Denotative and connotative meaning relations in the selection of canine lexicon in the Spy x Family anime series - Muhammad Yusuf; Muhammad Kiki Wardana (International Journal Linguistics of Sumatra and Malay, 2026)
This study investigates the denotative and connotative meaning relations of canine terminology in the anime Spy x Family Season 2 Episode 1 ("Mission 13: Project Apple") using Geoffrey Leech’s lexical semantics framework. Grounded in a descriptive qualitative method, textual data from spoken dialogues and monologues were gathered using observation and note-taking techniques. The analysis identifies seven distinct Japanese canine lexicons: Inu, Wan-chan, Inu-san, Banken, Bakudan-ken, Dougu, and Wan-kou. The findings reveal that while denotative meanings anchor literal reference, connotative layers span a wide evaluative spectrum reflecting speaker ideology. Affectionate and personified diction (Wan-chan, Inu-san) elevates the animal to an equal domestic companion, utilitarian terms (Banken) reflect pragmatic operational valuation, and derogatory expressions (Bakudan-ken, Dougu) result in extreme de-animation and objectification within terrorist discourse. This research concludes that lexical selection in fictional narratives acts as a crucial moral marker, establishing an ideological dividing line between humanistic empathy and utilitarian extremism.